Process Analysis of Integrated Biomass Gasification and Solid Oxide Electrolysis Cell (SOEC) for Syngas Production - Detchusananard, Thanaphorn; Wiranarongkorn, Kunlanan; Im-Orb, Karittha (My University, 2023)
The integrated biomass gasification and SOEC process (IBG-SOEC), which O2 from SOEC was used as gasifying agent while the separated H2 could be used for H2/CO adjustment or sell as a valuable byproduct, was studied to find the sustainable syngas production process. The model of IBG-SOEC was developed in Aspen Plus. The parametric analysis was performed to investigate the effect of operating conditions of SOEC (i.e., cell temperature and number of cells) on the overall process performance. For energy performance, the total energy demand decreased as cell temperature increased while increased with number of cells. The changes in cell temperature had no effect on the yield and composition of syngas from gasifier. The maximum yield of syngas, with H2/CO of 0.96, of 1.9 kmol/h was achieved at cell temperature of 790°C and number of cells of 600. At this condition, the overall efficiency of IBG-SOEC of 63 % was achieved and H2 byproduct of 1 kmol/h could obtained from SOEC.